1996
DOI: 10.1093/oxfordjournals.humrep.a019405
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinology: Iminunohistochemical study of steroidogenesis and cell proliferation in polycystic ovarian syndrome

Abstract: We evaluated the immunolocalization of the steroidogenic enzymes involved in the production of ovarian steroids, including the cholesterol side-chain cleavage enzyme (P450scc), 3beta-hydroxysteroid dehydrogenase (HSD), 17alpha-hydroxylase (P450c17) and aromatase (P450arom), oestrogen receptor (ER) and androgen receptor (AR), a steroidogenic transcription factor. Ad4-binding protein (Ad4BP) and a cell cycle-related nuclear antigen, Ki67, in five patients with polycystic ovarian syndrome (PCOS). Results were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 23 publications
2
40
0
5
Order By: Relevance
“…Decreased granulosa cell proliferation was also reported in bovine PCOS (Isobe & Yoshimura 2000). However, in studies carried out with PCOS women, either increased proliferation or no difference was found in granulosa cells of early antral follicles (4-8 mm diameter) in PCOS group compared with those in the control group (Takayama et al 1996, Stubbs et al 2007, Das et al 2008. The inconsistent results obtained from the human and rat may be due to the difference in the stage of the follicles examined.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Decreased granulosa cell proliferation was also reported in bovine PCOS (Isobe & Yoshimura 2000). However, in studies carried out with PCOS women, either increased proliferation or no difference was found in granulosa cells of early antral follicles (4-8 mm diameter) in PCOS group compared with those in the control group (Takayama et al 1996, Stubbs et al 2007, Das et al 2008. The inconsistent results obtained from the human and rat may be due to the difference in the stage of the follicles examined.…”
Section: Discussionmentioning
confidence: 90%
“…Although altered cell proliferation in PCOS granulosa cells has been documented by a number of studies (Takayama et al 1996, Isobe & Yoshimura 2000, Stubbs et al 2007, Das et al 2008, Salvetti et al 2009, the underlying mechanism is not well understood. Herein, we have found that CFTR is downregulated in granulosa cells of PCOS rats, accompanied by downregulation of the pro-proliferative gene Pcna.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of hyperandrogenism have been reported in patients with aromatase deficiency (51,52). Immunohistochemical studies of polycystic ovaries could not detect aromatase in antral follicles of various sizes (53). On the other hand it has been found that granulosa cells from anovulatory polycystic ovaries are hyperresponsive to follicle-stimulating hormone (FSH) in vitro, displaying significantly greater oestradiol production than granulosa cells from normal ovaries, suggesting no functional deficiency of aromatase in polycystic ovaries (54).…”
Section: The Aromatase Gene (Cyp19)mentioning
confidence: 99%
“…It has previously been reported that alterations in the content of steroid hormones in the cystic ovaries of women [5,6], rat [7] and cow [8] was accompanied by changes in the expression and cellular distribution pattern of cholesterol side-chain cleavage cytochrome (P450 scc ), 3β-hydroxysteroid dehydrogenase (3β-HSD), 17,20-lyase, 20α-HSD and/or aromatase cytochrome (P450 arom ). Furthermore, our pilot study showed that dexamethasone (DXM) injections in gilts from day 16 of the first studied estrous cycle until day 9 of the second studied cycle, lead to changes in the of P450 scc , 3β-HSD and P450 arom protein expression, as well as in the content of progesterone (P 4 ), androgens and estrogens in ovarian structures [9].…”
Section: Introductionmentioning
confidence: 99%